2020
DOI: 10.1038/s41467-020-16357-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Arctic permafrost carbon loss through stratospheric aerosol geoengineering

Abstract: The Arctic is warming far faster than the global average, threatening the release of large amounts of carbon presently stored in frozen permafrost soils. Increasing Earth's albedo by the injection of sulfate aerosols into the stratosphere has been proposed as a way of offsetting some of the adverse effects of climate change. We examine this hypothesis in respect of permafrost carbon-climate feedbacks using the PInc-PanTher process model driven by seven earth system models running the Geoengineering Model Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 76 publications
6
53
0
Order By: Relevance
“…Over half of the high latitude winter warming compared to the annual mean results from differences between SW and LW forcing which, as Govindasamy et al (2003) and Jiang et al (2019) point out, is especially prominent at high latitudes, and that cannot be avoided even if a more careful spatial distribution of the counteracting forcing is applied, as also suggested by Henry and Merlis (2020), who decomposed the vertical structure of the forcing in a single column model and found that inhomogeneities in the two forcings always result in some residual warming at high latitudes. To conclude, the observed differences between the analyzed simulations highlight a complex interplay of factors: the stratospheric heating directly affecting the surface climate through a modification of the North Atlantic Oscillation (Banerjee et al, 2020), the seasonality of the aerosol distribution (that in turn may be dynamically affected by the strengthening of the polar vortex, Visioni, MacMartin, ) and a fundamental difference between the LW and SW radiative forcings; all of these factors indicate that, when assessing the projected potential of stratospheric sulfate geoengineering to mitigate changes in high-latitudinal ecosystems with the potential to release considerable amounts of carbon (Chen et al, 2020), the inclusion of realistic aerosol behavior is crucial.…”
Section: Comparison Of Simulated Surface Temperatures and Precipitationmentioning
confidence: 99%
“…Over half of the high latitude winter warming compared to the annual mean results from differences between SW and LW forcing which, as Govindasamy et al (2003) and Jiang et al (2019) point out, is especially prominent at high latitudes, and that cannot be avoided even if a more careful spatial distribution of the counteracting forcing is applied, as also suggested by Henry and Merlis (2020), who decomposed the vertical structure of the forcing in a single column model and found that inhomogeneities in the two forcings always result in some residual warming at high latitudes. To conclude, the observed differences between the analyzed simulations highlight a complex interplay of factors: the stratospheric heating directly affecting the surface climate through a modification of the North Atlantic Oscillation (Banerjee et al, 2020), the seasonality of the aerosol distribution (that in turn may be dynamically affected by the strengthening of the polar vortex, Visioni, MacMartin, ) and a fundamental difference between the LW and SW radiative forcings; all of these factors indicate that, when assessing the projected potential of stratospheric sulfate geoengineering to mitigate changes in high-latitudinal ecosystems with the potential to release considerable amounts of carbon (Chen et al, 2020), the inclusion of realistic aerosol behavior is crucial.…”
Section: Comparison Of Simulated Surface Temperatures and Precipitationmentioning
confidence: 99%
“…Additionally, the impacts of these thaws will have very serious consequences: loss of coastal land under business as usual emissions scenarios has been costed at US$50 trillion/year (Hinkel et al, 2014), while building and maintaining coastal defences to prevent that loss of land would still cost about US$50 billion/year. The cost of carbon release from permafrost also runs in the trillion per year range – even assuming it would not cause outright civilization collapse (Chen et al, 2020; Yumashev et al, 2019). Loss of summer sea ice in the Arctic Ocean would have less dramatic impacts on the global environment, but would destroy or threaten many ecosystems and species.…”
Section: What Is Targeted Geoengineering?mentioning
confidence: 99%
“…However, this suggestion seems to neglect permafrost stability and thaw, which as stated earlier, would eventually release vast quantities of greenhouse gases that would undermine any global attempts at mitigating anthropogenic emissions. The upper 3m of permafrost contains twice the carbon than in the present atmosphere, but its release rate is uncertain in models (Chen et al, 2020) and highly dependent on rapid thaw (thermokarst) processes (Turetsky et al, 2020), which are not incorporated well into Earth System Models at present. Turetsky et al (2020) estimate that although thermokarst might only occur in 1/5 of the permafrost area, it would dominate overall carbon losses.…”
Section: Governance Of the Permafrostmentioning
confidence: 99%
“…There have been a number of simulations of “global” SAI strategies with the aim of maintaining a desired global mean temperature or other climate goals: The G3 and G4 experiments of the Geoengineering Model Intercomparison Project (GeoMIP) injected SO 2 above the equator to offset increases in radiative forcing and global mean temperature (Kravitz et al., 2011), and the Geoengineering Large Ensemble (GLENS) study injected SO 2 at 30°N, 15°N, 15°S, and 30°S independently to try and stabilize global mean temperature alongside the interhemispheric and equator‐to‐pole temperature gradients (Kravitz et al., 2017; Tilmes, Richter, Kravitz, et al., 2018). Several studies have evaluated the Arctic impacts of these “global” approaches, finding that low‐ or mid‐latitude injections of SO 2 could reduce global‐warming‐induced losses of sea ice and permafrost (Chen et al., 2020; Jiang et al., 2019; Lee et al., 2020; Moore et al., 2019). However, high‐latitude SAI intended specifically to preserve the Arctic has been hypothesized to provide greater Arctic cooling per unit of injection than low‐latitude SAI with smaller effects at low latitudes; for example, high‐latitude injections have been shown to have smaller impacts on tropical precipitation than equatorial injections (Sun et al., 2020).…”
Section: Introductionmentioning
confidence: 99%